Impact of Chest Compression Fraction on Outcomes in In-Hospital and Emergency Department Cardiac Arrests at a Tertiary Care Center in South India - K S Chanjal; R Haneendhar; M Senthil Kumar; Jinka Venkata Durgaprasad; B Sudhiersharan; Melvin Dominic; Panneerselvam Periasamy (Journal of Pharmacy and Bioallied Sciences)
Background: The study aimed to determine the average chest compression fraction (CCF) and its correlation with influencing factors to optimize blood flow during resuscitation, aiming for a minimum of 60%. Materials and Methods: Prospective observational study on 50 cardiac arrest patients, analyzing chest compression fraction (CCF) and identifying associations using Spearman’s correlation coefficient and individual student t-tests. Results: The study revealed a satisfactory average Chest Compression Fraction (CCF) of 71.66 ± 7.79, with diabetes mellitus being the most prevalent medical condition, and no significant correlation between compression depth, rate, and recoil. Conclusion: The average cardiac arrest (CCF) in ED patients decreased with longer code durations, daytime events, defibrillator use, increased team members, male providers, and chest compressions.